The cytoskeleton in the unique cell reproduction by conidiogenesis of the long-neck yeast Fellomyces (Sterigmatomyces) fuzhouensis - Gabriel, M; Kopecká, M; Yamaguchi, M; Svoboda, A; Takeo, K; Yoshida, S; Ohkusu, M; Sugita, T; Nakase, T (Protoplasma, 2006)
The morphology of conidiogenesis and associated changes in microtubules, actin distribution and ultrastructure were studied in the basidiomycetous yeast Fellomyces fuzhouensis by phase-contrast, fluorescence, and electron microscopy. The interphase cell showed a central nucleus with randomly distributed bundles of microtubules and actin, and actin patches in the cortex. The conidiogenous mother cell developed a slender projection, or stalk, that contained cytoplasmic microtubules and actin cables stretched parallel to the longitudinal axis and actin patches accumulated in the tip. The conidium was produced on this stalk. It contained dispersed cytoplasmic microtubules, actin cables, and patches concentrated in the cortex. Before mitosis, the nucleus migrated through the stalk into the conidium and cytoplasmic microtubules were replaced by a spindle. Mitosis started in the conidium, and one daughter nucleus then returned to the mother via an eccentrically elongated spindle. The cytoplasmic microtubules reappeared after mitosis. A strong fluorescence indicating accumulated actin appeared at the base of the conidium, where the cytoplasm cleaved eccentrically. Actin patches then moved from the stalk together with the retracting cytoplasm to the mother and conidium. No septum was detected in the long neck by electron microscopy, only a small amount of fine "wall material" between the conidium and mother cell. Both cells developed a new wall layer, separating them from the empty neck. The mature conidium disconnected from the empty neck at the end-break, which remained on the mother as a tubular outgrowth. Asexual reproduction by conidiogenesis in the long-neck yeast F. fuzhouensis has unique features distinguishing it from known asexual forms of reproduction in the budding and fission yeasts. Fellomyces fuzhouensis develops a unique long and narrow neck during conidiogenesis, through which the nucleus must migrate into the conidium for eccentric mitosis. This is followed by eccentric cytokinesis. We found neither an actin cytokinetic ring nor a septum in the long neck, from which cytoplasm retracted back to mother cell after cytokinesis. Both the conidium and mother were separated from the empty neck by the development of a new lateral wall (initiated as a wall plug). The cytoskeleton is clearly involved in all these processes.
Keywords: buněčné dělení; Basidiomycota; cytoskelet; Microscopy, Fluorescence; Cytoskeleton; Microtubules; mikroskopie fázově kontrastní; Actins; Cell Division; aktiny; fluorescenční mikroskopie; buněčný cyklus; Cell Cycle; Microscopy, Electron, Transmission; mikrotubuly; transmisní elektronová mikroskopie; Microscopy, Phase-Contrast